2011
DOI: 10.4103/0259-1162.94759
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal nalbuphine as an adjuvant to subarachnoid block: What is the most effective dose?

Abstract: Background:Nalbuphine has been used intrathecally as an adjuvant in previous studies, but none clearly state the most effective dose of nalbuphine. The purpose of our study was to establish the effectiveness of intrathecal nalbuphine as an adjuvant, compare three different doses and determine the optimum dose with prolonged analgesic effect and minimal side-effects.Materials and Methods:In this prospective, randomized, double-blinded, controlled study, 100 ASA I and II patients undergoing lower limb orthopedic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 18 publications
3
24
0
Order By: Relevance
“…The same result reported by Tiwari et al [18] but by using smaller dose (0.2 and 0.4 mg) . Supporting the previous results, Ahmed et al [19] concluded that significant increase in postoperative duration of analgesia compared with the vehicle-treated group in abdominal operation following administration of intrathecal nalbuphine in doses of 0.8,1.6 and 2.4 mg .The same results were obtained by both Kumaresan and Raj [20] and Mukherjee et al [21] who used 0.4, 0.8 mg of intrathecally nalbuphine in patients scheduled in optional lower limb surgeries and show significant analgesia prolongation. On the other hand, Verma et al [22] concluded intrathecal nalbuphine 2 mg is effective in enhancing postoperative analgesia compared to bupivacaine alone or along with tramadol.…”
Section: Discussionsupporting
confidence: 57%
“…The same result reported by Tiwari et al [18] but by using smaller dose (0.2 and 0.4 mg) . Supporting the previous results, Ahmed et al [19] concluded that significant increase in postoperative duration of analgesia compared with the vehicle-treated group in abdominal operation following administration of intrathecal nalbuphine in doses of 0.8,1.6 and 2.4 mg .The same results were obtained by both Kumaresan and Raj [20] and Mukherjee et al [21] who used 0.4, 0.8 mg of intrathecally nalbuphine in patients scheduled in optional lower limb surgeries and show significant analgesia prolongation. On the other hand, Verma et al [22] concluded intrathecal nalbuphine 2 mg is effective in enhancing postoperative analgesia compared to bupivacaine alone or along with tramadol.…”
Section: Discussionsupporting
confidence: 57%
“…The mean time taken to achieve maximum motor block of Bromage 3 was earlier in Group N, but the results were comparable and statistically nonsignificant. In a study done by Mukherjee et al .,[ 13 ] it was seen that onset of motor block was early in group containing 0.8 mg nalbuphine and duration of motor block was also more in that group, but the difference was insignificant as seen in our study also. In a study done by Jain et al .,[ 14 ] it was observed that there was early onset of motor block in ketamine group along with longer duration of motor block although the difference was insignificant, as observed in our study.…”
Section: Discussionsupporting
confidence: 48%
“…compared 0.2, 0.4, and 0.8 mg of intrathecal nalbuphine in lower limb orthopedic surgery and recommended 0.4 mg of nalbuphine as the optimal dose without any side effects. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%